Taxonomic Observation of a New Species of the Genus Moniezia Blanchard, 1891 from Capra hircus Linnaeus, 1758 - Somnath, Waghmare (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT A new species of the genus Monieza Blanchard, 1891 i.e. Moniezia (B) mansurae Sp.Nov were collected from Capra hircus Linnaeus, 1758 from different sites of Aurangabad district (MS) INDIA. The present parasite form of worm is differs from all known species of the genus Moniezia Blanchard, 1891 in having length of worm, number and shape of testes, shape of cirrus pouch, shape of ovary, position of vagina and number of Interproglottidal glands. Key words- Capra hircus, Moniezia, Taxonomic Observation,Aurangabad district